IDENTIFYING PSYCHOLOGICAL SUBJECT AS A THEME: FOCUSING ON ENGLISH DECLARATIVE CLAUSES - Puspita Sari; Diana Anggraeni (Berumpun: International Journal of Social, Politics, and Humanities, 2020)
This research discusses one of the types of subjects functioning as a theme proposed by Halliday (1985) in the English Declarative Clause which is called the Psychological Subject. Halliday claims the interpretation of Psychological subject into as something which is the concern of the message. It is the first constituent which becomes a ‘subject-matter’ of the clause. The data are taken from two kinds of books. The first one is an autobiography book and the second one is a medical book. The aim of this research is to identify the kinds of the theme found in psychological subjects in the English Declarative Clause and also categories found in psychological subjects functioning as a theme. The method used is a descriptive method and the technique employed is paraphrasing. The descriptive method was used to depict the empirical data discovered in those sources. Meanwhile, the paraphrasing technique was employed in order to explore the characteristics of psychological subject functioning as a theme, types of theme and categories of syntactic units. The study shows that Psychological Subject (PS) functioning as a theme can be filled by words and groups which could be realized by nominal groups (nouns and pronouns), nominal group complexes, adverbial groups or prepositional phrases. Nominal groups (nouns and pronouns) and nominal group complexes can be identified as unmarked themes which are ordinary, expected, and usual form according to Deterding (2001), Gerot and Wignel (1994) identified as the subject of the sentence. Meanwhile, adverbial groups and prepositional phrases could be identified as marked themes because they become the first constituents which perform the point of the departure of the message in the clause.